Patients Present with Left Bundle Branch Block and its Cardiac Structure Disease during Trans Thoracic Echocardiography - Irfan Ali Arbab, Faraz Farooq Memon, Muhammad Rafique, Sharwan Bhuro Mal, Ghulam Kubra, Shazia Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Purpose: Left bundle branch block (LBBB) is a communal electrocardiographic (ECG) finding that may or may not be associated with overt heart disease at diagnosis. The current study was performed to determine the clinical picture and structural abnormalities of the heart diagnosed by transthoracic echocardiography in patients with left bundle branch block. Methods: This cross-sectional observational study was conducted over a six-month period in the Interventional Cardiology Unit Liaquat University Hospital Hyderabad from July 2021 to December 2021. Adult patients of both sexes with LBBB, symptomatic or asymptomatic, were recruited from an outpatient hospital setting and underwent elective Transthoracic echocardiography (TTE) after demographic / clinical data and informed consent were obtained. The TTE results were recorded and presented as frequency and percentage. Results: 120 patients were examined; 74 men and 46 women. The study population mean age was 52.7 ± 1.5 years, range (22-76) years. In a history, 10 (8.3%) patients had mild dyspnoea (NYHA class I-II) and 9 (7.5%) severe dyspnoea (NYHA class III-IV). Echocardiograms of only 11 (9.2%) patients were normal. The structural abnormalities observed included abnormal septal motion in 96 (80%), mitral regurgitation in 16 (13.3%), and left ventricular dilatation with left ventricular end-diastolic dimension> 60 mm in 23 (19.2%). LVEF was normal in 80 (66.7%) cases (> 50%); 18 (15%) had a LVEF of 25-35% and 12 (10%) had a LVEF of 35-50%. Conclusion: The possibility of structural cardiac abnormalities on echocardiography is high in patients with LBBB.